Management of Post Burn Contracgture Using Tensor Fascia Lata Myocutaneous Flap - Verma, Pramod Kumar (Indian Journal of Plastic Surgery, 1986)
Role of Tensor Fascia Lata myocutaneous flap in the management of a grain contracture has been evaluated. Its advantages and merits have been discussed alongwith a review of the literature.